Feasibility of cardiac-synchronized quantitative T1 and T2 mapping on a hybrid 1.5 Tesla magnetic resonance imaging and linear accelerator system. (January 2022) - Akdag, Osman; Mandija, Stefano; van Lier, Astrid L.H.M.W.; Borman, Pim T.S.; Schakel, Tim; Alberts, Eveline; van der Heide, Oscar; Hassink, Rutger J.; Verhoeff, Joost J.C.; Mohamed Hoesein, Firdaus A.A.; Raaymakers, Bas W.; Fast, Martin F.
Abstract: Background and Purpose: The heart is important in radiotherapy either as target or organ at risk. Quantitative T1 and T2 cardiac magnetic resonance imaging (qMRI) may aid in target definition for cardiac radioablation, and imaging biomarker for cardiotoxicity assessment. Hybrid MR-linac devices could facilitate daily cardiac qMRI of the heart in radiotherapy. The aim of this work was therefore to enable cardiac-synchronized T1 and T2 mapping on a 1.5 T MR-linac and test the reproducibility of these sequences on phantoms and in vivo between the MR-linac and a diagnostic 1.5 T MRI scanner. Materials and methods: Cardiac-synchronized MRI was performed on the MR-linac using a wireless peripheral pulse-oximeter unit. Diagnostically used T1 and T2 mapping sequences were acquired twice on the MR-linac and on a 1.5 T MR-simulator for a gel phantom and 5 healthy volunteers in breath-hold. Phantom T1 and T2 values were compared to gold-standard measurements and percentage errors (PE) were computed, where negative/positive PE indicate underestimations/overestimations. Manually selected regions-of-interest were used for in vivo intra/inter scanner evaluation. Results: Cardiac-synchronized T1 and T2 qMRI was enabled after successful hardware installation on the MR-linac. From the phantom experiments, the measured T1 /T2 relaxation times had a maximum percentage error (PE) of −4.4%/−8.8% on the MR-simulator and a maximum PE of −3.2%/+8.6% on the MR-linac. Mean T1 /T2 of the myocardium were 1012 ± 34/51 ± 2 ms on the MR-simulator and 1034 ± 42/51 ± 1 ms on the MR-linac. Conclusions: Accurate cardiac-synchronized T1 and T2 mapping is feasible on a 1.5 T MR-linac and might enable novel plan adaptation workflows and cardiotoxicity assessments.